Fra selfangstskuter til vitenskapelige ekspedisjonsskip. Svend Foyn og ishavsekspansjonen fra Sør-Norge - Christensen, Olav (Norsk sjøfartsmuseum. Årbok, 2007)
Keywords: Carl Anton Larsen; Nordmenn; Sørishavet; Vestfold; ekspedisjoner; fangst; hvalfangere; hvalfangst; oppdagelsesreiser; polarområdene; vitenskap

Pioneer whalers in the Ross Sea, 1923–33 - Barr, William; Watt, James P C (Polar Record, 2005)
On Christmas Eve 1923, the whaling factory ship Sir James Clark Ross, commanded by Captain Carl Anton Larsen and accompanied by five catchers, reached the front of the Ross Ice Shelf; these were the first whaling vessels to operate in the Ross Sea. They had been dispatched by the Norwegian whaling company Hvalfangeraktienselskapet Rosshavet, which had obtained a licence from the British government. For most of the 1923–24 season, Sir James Clark Ross occupied an uneasy anchorage in the deep waters of Discovery Inlet, a narrow embayment in the front of the Ross Ice Shelf, while her catchers pursued whales widely in the Ross Sea. During that first season they killed and processed 221 whales (211 blue whales and 10 fin whales), which yielded 17,300 barrels of oil. During the next decade, with the exception of the 1931–32 season, Sir James Clark Ross and two other factory ships operated by Rosshavet, C.A. Larsen and Sir James Clark Ross II, operated in the Ross Sea. From the 1926–27 season onwards these ships were joined by up to three other factory ships and their catchers, operated by other companies. During the decade 1923–33 the Rosshavet ships killed and processed 9122 whales in the Ross Sea sector, mainly in the open waters of the Ross Sea south of the pack-ice belt. Total harvest for all factory ships from the Ross Sea sector for the period was 18,238 whales (mainly blue whales) producing 1,490,948 barrels of oil. From 1924 onwards the Rosshavet catchers wintered in Paterson Inlet on Stewart Island, New Zealand, and from 1925 onwards a well-equipped shipyard, Kaipipi Shipyard, operated on Price Peninsula in Paterson Inlet to service the Rosshavet ships.
Keywords: Carl Anton Larsen; Rosshavet; Sørishavet; hvalfangere; hvalfangstselskaper; pelagisk

Rosshavets base på Stewart Island - Hoff, Stein (Norsk sjøfartsmuseum. Årsberetning, 1987)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; historie; hvalfangere; hvalfangststasjoner; pelagisk

Noen problemer i den moderne hvalfangsts historie - Tønnessen, Johan Nicolay (Vestfold-minne, 1964)
Keywords: Carl Anton Larsen; Henrik Johan Bull; Svend Foyn; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalindustri; næring; pelagisk; polareksspedisjoner; økonomi

De første norske oppdagelser i Sørishavet - Aagaard, Bjarne (Nordmannsforbundet, 1943)
Keywords: Carl Anton Larsen; Sørishavet; ekspedisjoner; oppdagelsesreiser

Hjemkomsten. Hvlafangsten historie fra dens første begynnelse - Istre, Henry R (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Sørishavet; historie; hvalfangere; hvalfangst; pelagisk

Recent Antarctic discoveries - Brown, R N Rudmose (Scottish Geographical Magazine, 1929)
Keywords: Antarktis; Carl Anton Larsen; Jason (skip); hvalfangere; oppdagelsesreiser

Antarctics sidste Færd. Foredrag den 18de februar 1904 - Larsen, Carl Anton (Det Norske geografiske selskabs aarbok, 1904)
Keywords: Antarctic (skip); Antarktis; Carl Anton Larsen; Den svenske antarktisekspedisjonen 1901–03; Otto Nordenskjöld; Sørishavet; vitenskapelige ekspedisjoner

The Antarctic Expeditions - Markham, Clements (The Geographical Journal, 1899)
Keywords: Antarktis; Carl Anton Larsen; Jason (skip); ekspedisjoner; oppdagelsesreiser

Begleitworte zur Karte des Dirck Gherritz Archipels - Friedrichsen, Ludwig (Mitteilungen der Geographischen Gesellschaft in Hamburg, 1895)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; Vestantarktis; ekspedisjoner; geografi; geologi; oppdagelsesreiser

Kapit. Larsens antarktische Entdeckungen - Petersen, J; Larsen, Carl Anton; Wichmann, Hugo (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1895)
Keywords: Antarktis; Carl Anton Larsen; ekspedisjoner; forskning; geografi; geologi; hvalfangere; oppdagelsesreiser

Die Reisen des "Jason" und der "Hertha" in das Antarktische Meer 1893/94 : und die wissenschaftliche Ergebnisse dieser Reisen - Petersen, Johannes; Friedrichsen, Ludwig (Mitteilungen der Geographischen Gesellschaft in Hamburg, 1895)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; Hertha (skip); Vestantarktis; dagbok; ekspedisjoner; forskning; geologi; hvalfangere; oppdagelsesreiser

Das Wiedererwachen der antarktischen Forschung - Wichmann, Hugo; [Hassenstein, Bruno] (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1895)
Keywords: Antarktis; Carl Anton Larsen; D/S Antarctic; ekspedisjoner; forskning; geografi; geologi; hvalfangere; oppdagelsesreiser

Captain Larsen's Antarctic Journal - Cocks, Alfred Heneage (The Geographical Journal, 1894)
Keywords: Carl Anton Larsen; D/S Jason; Sørishavet; dagbok; ekspedisjoner; hvalfangere; oppdagelsesreiser

Nogle optegnelser af sæl- og hvalfanger Jason's reise i Sydishavet 1893 og 94 - Larsen, Carl Anton (Det Norske geografiske selskabs aarbok, 1894)
Keywords: Carl Anton Larsen; D/S Jason; Sørishavet; ekspedisjoner; hvalfangere; oppdagelsesreiser

The Voyage of the "Jason" to the Antarctic Regions : abstract of journal kept by Capt. C. A. Larsen - Larsen, Carl Anton (The Geographical Journal, 1894)
Keywords: Carl Anton Larsen; D/S Jason; Sørishavet; dagbok; ekspedisjoner; hvalfangere; oppdagelsesreiser

Notes on an important geographical discovery in the Antarctic Regions - Murray, John (Scottish Geographical Magazine, 1894)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; Vestantarktis; dagbok; ekspedisjoner; forskning; geografi; geologi; hvalfangere; oppdagelsesreiser

Das neu entdeckte Land im antarktischen Gebiet - Schück, Albert (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1894)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; dagbøker; ekspedisjoner; forskning; geografi; geologi; hvalfangere; oppdagelsesreiser